Food policies and obesity in low and middle income countries - Abay, Kibrom A.; Ibrahim, Hosam; Breisinger, Clemens (International Food Policy Research Institute, 2020)
Understanding the public health implication of fiscal policies is crucial to combat recently increasing overweight and obesity rates in many low-and-middle income countries (LMICs). This study examines the implication of food policies, mainly tariff rates on “unhealthy” foods, including sugar and confectionery products as well as fats and oils, and governments’ subsidies on individuals’ body weight outcomes. We compile several macro- and micro-level datasets that provide for several LMICs macro-level information on food policies and micro-level anthropometric data. We exploit temporal dynamics in tariff rates on “unhealthy” foods and governments’ spending on subsidies to estimate fixed effects models characterizing the evolution of body weight outcomes. We find that temporal dynamics in tariff rates on unhealthy and energy-dense foods are significantly and negatively associated with body weight. Conditional on several observable and time-invariant unobservable factors, a decrease in tariff rates on sugar and confectionary foods or fats and oils is associated with an increase in overweight and obesity rates. On the other hand, an increase in subsidy rates, as a share of government expenditure, is significantly associated with higher overweight and obesity rates. Interestingly, we find that the implications of these food policies are more pronounced among poorer individuals. This is intuitive because relatively poorer households are more likely to spend a larger share of their income on food consumption or unhealthy foods, and these types of households are beneficiaries of government subsidies in many LMICs. These findings have important implications for informing public health policies in LMICs, which are experiencing an unprecedented rise in overweight and obesity rates.